Psychological problems associated with diagnosis and treatment of lymphomas. II: Prospective study. Issue 6604 (17th October 1987) - Devlen, J; Maguire, P; Phillips, P; Crowther, D
Abstract : A prospective study of 120 patients newly diagnosed as having Hodgkin's disease and non-Hodgkin's lymphoma was conducted to determine the nature, extent, and timing of the psychiatric and social morbidity associated with the diagnosis and treatment. Patients were interviewed at diagnosis and two, six, and 12 months later by trained interviewers using standardised questionnaires. Psychiatric morbidity was greatest in the three months before treatment, but new episodes of anxiety and depression developed throughout the year of follow up. Altogether 39 patients suffered a depressive illness or anxiety state, or both, and a further 37 experienced borderline anxiety or depression, or both, during the 15 months of assessment. The most common adverse effects of treatment were hair loss, nausea, vomiting, sore mouth, and changes in perception of taste. Toxicity of treatment was associated with psychiatric morbidity. Conditioned responses to chemotherapy were experienced by 32 patients. Social morbidity was low, although difficulties in returning to work and to previous levels of leisure activity were noted. Although most patients were no longer receiving treatment and were free of disease at the one year follow up, 51 patients continued to complain of loss of energy, 24 of loss of libido, 38 of tiredness, 23 of irritability, 18 of poor concentration, and 23 of memory impairment. These results confirm our retrospective study and suggest that a high price is paid for long term survival by a substantial proportion of patients receiving treatment for Hodgkin's disease and non-Hodgkin's lymphoma.